4y+3(y-2)=7y-2(y-10)

Simple and best practice solution for 4y+3(y-2)=7y-2(y-10) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4y+3(y-2)=7y-2(y-10) equation:


Simplifying
4y + 3(y + -2) = 7y + -2(y + -10)

Reorder the terms:
4y + 3(-2 + y) = 7y + -2(y + -10)
4y + (-2 * 3 + y * 3) = 7y + -2(y + -10)
4y + (-6 + 3y) = 7y + -2(y + -10)

Reorder the terms:
-6 + 4y + 3y = 7y + -2(y + -10)

Combine like terms: 4y + 3y = 7y
-6 + 7y = 7y + -2(y + -10)

Reorder the terms:
-6 + 7y = 7y + -2(-10 + y)
-6 + 7y = 7y + (-10 * -2 + y * -2)
-6 + 7y = 7y + (20 + -2y)

Reorder the terms:
-6 + 7y = 20 + 7y + -2y

Combine like terms: 7y + -2y = 5y
-6 + 7y = 20 + 5y

Solving
-6 + 7y = 20 + 5y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-5y' to each side of the equation.
-6 + 7y + -5y = 20 + 5y + -5y

Combine like terms: 7y + -5y = 2y
-6 + 2y = 20 + 5y + -5y

Combine like terms: 5y + -5y = 0
-6 + 2y = 20 + 0
-6 + 2y = 20

Add '6' to each side of the equation.
-6 + 6 + 2y = 20 + 6

Combine like terms: -6 + 6 = 0
0 + 2y = 20 + 6
2y = 20 + 6

Combine like terms: 20 + 6 = 26
2y = 26

Divide each side by '2'.
y = 13

Simplifying
y = 13

See similar equations:

| x^6-3x^5+x-3= | | 8(V+2)-2V=2(3V+2)-6 | | 13/5y=8 | | 9+3s-6=8s+5-3s | | 9y=10y-4 | | 1x(5x+2)=3 | | 2n/5-2/7=18/35 | | x^2=2x-24 | | 5a-12a=7-2a | | 5(2x+9)=-37+22 | | 4x+5+10x-25=90 | | -0.2x=1 | | 800-45x+.10x^2=0 | | 7x+14+x=180 | | 2(x-7)+2x=4(x+8)-46 | | 2X^2-10X-90=0 | | Ln(3x*2x)=3 | | 3x+8-5(x+1)=7x+5 | | 33a+12=7900 | | y=3/4(4)-6 | | y-16+10x-25=180 | | 12-54=-3x-6x | | 7.5=2+1.5(3x+1) | | 2(5x+3)=18 | | .02-.02(x+3)=-.03(3-x) | | 3n+6=33 | | n+7=7+n | | .16(24)+.04x=.08(6+x) | | 6m+3=9 | | 3x-59=-1 | | solvex=3y+10fory | | 2(X-8)=2X-16 |

Equations solver categories